THE PROCESSING OF WHITE PEPPER BY FERMENTATION THROUGH SOAKING TIME AND CONCENTRATION OF Bacillus Subtilis INOCULUM ON QUALITY AND OFF FLAVOUR CONTENT - Hernani, Hernani; Yumma, Haura Latifa; Aminingsih, Tri (Jurnal Penelitian Pascapanen Pertanian, 2021)
The processing of white pepper is still done traditionally, namely by soaking in unclean water that it can cause product contamination by unwanted microorganisms. The present work was to find out the effect of white pepper processing by fermentation using Bacillus subtilis inoculum through the length of soaking time and concentration of the inoculum on the quality and off-flavor compounds. The research method was carried out in several stages, namely the preparation of B. subtilis inoculum, preparation of raw materials, fermentation of pepper, decortication, drying using an oven at 50 Â° C, analysis of quality and of off flavor compounds. The results showed that the soaking time has a significant effect on the content of light pepper, piperine, essential oil, and the color of the pepper. The concentration of B. subtilis inoculum has a significant effect on the quality of piperine, essential oil, and pepper color. The interaction between the soaking time and B. subtilis concentration has significantly affected the quality of piperine and essential oil levels. The soaking time of pepper for 7 days and the varying concentration of B. subtilis inoculums produced better quality pepper compared to the length of soaking for 5 days. White pepper with the lowest TPC value was from soaking for 5 days with B. subtilis inoculum concentration of 20% was 1.86x103 CFU / g. From the analysis of off-flavor compounds in the 5-days fermentation were identified 4 off flavor compounds, i.e., propanoic, butanoic, hexanoic acids and piperonal, while the 7-days with the same compound and the addition of 2 other compounds, namely p-cresol and 2 H methyl indole.